Pengelupasan Kulit Batang dan Penggunaan Zat Pengatur Tumbuh (ZPT) pada Stek Bugenvil (Bougainvillea spectabilis Willd.): Exfoliation of Stem Bark and Application of Plant Growth Regulation (PGR) on Bougainvillea Cuttings - Mutiara Dewi Puspitawati; Nurfitriyani Barokah (Politeknik Pertanian Bogor, 2023)
Exfoliating the stem bark and giving PGR is an alternative to increasing the success of bougainvillea cuttings. The aim of the study was to determine the success rate and growth rate of bougainvillea cuttings by exfoliating the bark and administering various PGRs. The research was conducted from March to July 2020 at the Trilogy University Experimental Garden, South Jakarta. This study used a Split-Plot Randomized Block Design with two factors, namely peeling factor (peeling and without peeling) and providing various ZPT (control, Rootone F 10 g L-1, shallot extract 200 g L-1, bean sprout extract 200 g L -1, and young coconut water). The results showed that the combination of stem bark peeling and shallot juice soaking was able to increase the proportion of pink bougainvillea (Bougainvillea spectabilis Willd.) cuttings growing by up to 87% compared to Rootone F immersion. Peeling treatment without providing various sources of PGR and treatment without peeling by soaking in shallot juice gave the fastest shoot emergence time, namely 10 HST. The stem peeling treatment was able to increase the number of shoots and the number of leaves on bougainvillea cuttings. Providing various kinds of PGRs (with a single treatment) can increase the number of leaves, number of shoots and shoot length on bougainvillea cuttings.